INNOVATIVE UTILIZATION OF SOIL AMENDMENTS FOR IMPROVING RESISTANCE IN OKRA AGAINST MELOIDOGYNE INCOGNITA - QAMAR , U; ALI , MA; ABDULLAH , M; ABDULLAH , MT; IQBAL , MM; NAZ , T; NAWAZ , S; ZAFAR , H; NAZIR , Q; LATIF , MI; AMIN , HAB; AAS , MA; et al. (Biological and Clinical Sciences Research Journal, 2024)
Okra productivity is significantly hindered by various pests and pathogens, including bacteria, fungi, and nematodes, particularly Meloidogyne incognita, which poses a severe threat to plant growth and yield. This study aimed to evaluate the efficacy of different organic and inorganic soil amendments—poultry manure (PM), farmyard manure (FYM), biochar, and rock phosphate (RP)—in managing Meloidogyne incognita in okra cultivation. A completely randomised design (CRD) with factorial arrangements and three replications was used to test two concentrations of each amendment: FYM (5%, 10%), biochar (0.5%, 1%), RP (2.5%, 5%), and PM (5%, 10%). Soil treatments were analysed for their effects on key growth parameters, including root weight, shoot weight, shoot dry weight, root length, plant height, number of leaves, and chlorophyll content. The findings revealed that FYM at 5% significantly enhanced root weight, shoot weight, and shoot dry weight (p ≤ 0.05). PM at 5% showed the greatest impact on root length, while FYM at 10% resulted in the highest plant height. Additionally, FYM at 5% contributed to the maximum number of leaves and chlorophyll content. Farmyard manure demonstrated superior performance compared to poultry manure, biochar, and rock phosphate in improving growth parameters and mitigating the effects of Meloidogyne incognita in okra cultivation. FYM at 5% and 10% concentrations proved to be the most effective treatments, suggesting its potential as a sustainable management strategy for nematode infestations in okra.